2017
DOI: 10.4236/ojog.2017.713133
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Educational Materials on the Duration of Exclusive Breastfeeding Assured by Women Who Delivered at the Souissi Maternity Hospital in Rabat

Abstract: Background: The practice of exclusive breastfeeding (EB) in Morocco has witnessed a worrying decline in recent decades, contrary to the recommendations of the World Health Organization (WHO) which advocates it during the first six months as a significant public health tool. The present study aims to assess the impact of educational materials on mothers' behaviour with regard to keeping up EB as long as six months, at least. Methods: This is a cohort study with a prospective collection of data over a period of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The level of education also influences the level of understanding and appropriation of public health messages [18]. Concerning practices of mothers, our survey showed that the percentage of early breastfeeding during the first half hour (53.4%, table 3) considerably exceeded the percentage reported in a similar single-center study carried out in the same hospital center with a percentage of 11.4% [19]. In addition, almost half of mothers have practiced skin-to-skin contact with their infant (43.1%, Table 4) and the majority of mothers plan to breastfeed exclusively until 6 months and even continue breastfeeding until 24 months.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The level of education also influences the level of understanding and appropriation of public health messages [18]. Concerning practices of mothers, our survey showed that the percentage of early breastfeeding during the first half hour (53.4%, table 3) considerably exceeded the percentage reported in a similar single-center study carried out in the same hospital center with a percentage of 11.4% [19]. In addition, almost half of mothers have practiced skin-to-skin contact with their infant (43.1%, Table 4) and the majority of mothers plan to breastfeed exclusively until 6 months and even continue breastfeeding until 24 months.…”
Section: Discussionmentioning
confidence: 67%
“…The results of this study clearly demonstrated that there are gaps in women's knowledge about SARS-CoV-2 infection during gestation and postpartum. In addition, this study also revealed that mothers as a group at high risk of postpartum mental disorders require mental health and psychosocial support during the period of the pandemic because current scientific evidence suggests that in this context a long-term psychological distress can affect both mothers and infants and the risks to infants may extend into infancy during the coronavirus (COVID- 19)…”
Section: Discussionmentioning
confidence: 86%
“…A multicomponent intervention (prenatal breastfeeding education, professional, and peer support programme) in Lebanon reported women in the intervention group were twice as likely to exclusively breastfeed compared to the control group in multivariate analysis (OR 2.02; 95% CI 1.20–3.39; P = 0.008) (Nabulsi et al, 2019 ). A post-natal breastfeeding educational session in Morocco resulted a significantly higher percentage of mothers in the intervention group exclusively breastfeeding their infants at six months compared to the control group, 55.2%; 38.8% respectively; P = 0.002 (Bennis et al, 2017 ). A health-centre based training programme for health professionals in Tunisia showed a significantly higher rate of exclusive breastfeeding at six months for women attending the intervention group health center compared to the control group: 11.0%, 4.3% respectively, P = 0.0001 (Chaouachi et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…Support and motivation should be provided to Mothers of preterm infants immediately after birth by health professionals with BF knowledge B.) Individual teaching methods, the use of developmental BF and follow up are effective in promoting BF Baih ( 2020 ) Postnatal primipara mothers and their live newborns Cairo, Egypt Pre- and post-intervention study N = 162 Nursing multicomponent intervention, including BF Follow-up at 4 weeks Knowledge and practice of mothers regarding BF There was an increase in maternal satisfaction pre- and post-intervention (p < 0.05), as follows: Pre-lactal feeding from 64.3% to 71% Colostrum feeding 56.2% to 81.5% EBF from 40.7% to 95.1% BF practice from 24% to 69.1% The implementation of nursing intervention sessions positively impacted hew mothers’ home care, as they reported increased satisfaction in BF practices Intervention classes for new mothers is recommended and should be included on as systematic basis Bashour et al ( 2008 ) New mothers Damascus, Syria Randomized controlled trial N = 876 IG (A): n = 285, 4 visits IG (B), n = 294, 1 visit CG: n = 297, No visit Multicomponent education program, including BF, delivered through postnatal home visits Follow-up at 4-months post-partum Proportion of new mothers who practiced of EBF Follow-up after 4 months The proportion of new mothers in IG A and B who exclusively breastfed their infants (28.5% and 30%, respectively) was increased compared with Group C (20%) Home visits after delivery lead to increase of EBF Other innovative methods are recommended to improve postnatal care in Syria Bennis et al ( 2017 ) Pregnant women Rabat, Morocco Prospective cohort study IG: n = 372 CG: n = 178 Educational sessions about benefits and management of BF (oral and written information) Six months follow-up through telephone EB rates 55.2% of IG exclusively breastfed their babies up to the age of six months compared to 38.8% in CG (p = 0.002) This strategy is effective in promoting EBF up to six months Development of an intervention program for health professionals to promote BF through pre- and post- natal education of mothers Khresheh et al ( 2018 ) ...…”
Section: Methodsmentioning
confidence: 99%